2022
DOI: 10.1002/jmv.27997
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of healthcare workers with COVID‐19 pre‐ and postvaccination

Abstract: Vaccines are the most effective strategy to control the spread of coronavirus disease‐2019 (COVID‐19). Data on COVID‐19 among healthcare workers (HCW) pre‐ and postvaccination are limited. This study aims to evaluate the clinical characteristics and outcomes of HCW with COVID‐19 pre‐ and postvaccination. Retrospective cohort study. All HCWs with suspected COVID‐19 were included. Demographic data, occupation, symptoms, work in COVID‐19 area, and vaccination status were collected. There were 22 267 HCW visits fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
1
2
0
2
Order By: Relevance
“…Finally, in this study, the analysis of clinical outcomes strengthens the good results already found in the past in the same cohort and confirmed by the literature data [25,40]. In particular, we observed only two hospitalizations, one of which in the intensive care unit and no deaths.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, in this study, the analysis of clinical outcomes strengthens the good results already found in the past in the same cohort and confirmed by the literature data [25,40]. In particular, we observed only two hospitalizations, one of which in the intensive care unit and no deaths.…”
Section: Discussionsupporting
confidence: 92%
“…Among them, the mRNA vaccine mRNABNT162b2 (Comirnaty ® ) has been widely employed in the Italian population ( 4 ). Several studies showed that mRNA vaccines help protect from severe COVID-19 disease, hospitalization and death in immunocompetent individuals and in frail populations ( 5 , 6 ). However, multiple sclerosis (MS) disease modifying therapies (DMTs) might affect COVID-19 disease severity as well as the development of humoral and cellular immunity after SARS-CoV-2 exposure or vaccination ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Not only the change in SARS-CoV-2 variants but also the introduction of COVID-19 vaccines has influenced headache prevalence in the acute phase of COVID-19. Although studies are limited, vaccinated people report less headache than those unvaccinated [30]. Several studies describe headache being more frequent in women [19,23,[31][32][33], at a younger age [19,34,35] and in patients with personal history of migraine [23,36,37].…”
Section: Q1 Is Headache And/or Facial Pain a Common Symptom Of Covid-...mentioning
confidence: 99%